Public policies, current challenges and changing scenarios - Pacheco Romero, Luis (2019)
The aim of this article is to think about public policies, their nature, and the role the State is to perform. Public policies show a way to people, and given the complex nature of social, economic and political reality, a topic to be studied is the quality of policies. Reality is in continuous change and processes can present surprising turns. International scene is under transformation. This and the need to achieve the Sustainable Development Goals add up to be a big challenge. In this context, an adequate tool for public policies is development planning.